Adolf Hitler : ses aspirations, sa politique, sa propagande, et les "Protocoles des sages de Sion" - Blank, R. M. (Rubin Markovich), 1866-1954 (L. Beresniak, 1938)
Describes the "Protocols" as a forgery of the tsarist police devised for tsarist propaganda. Hitler now uses this book for his own propaganda purposes, to further his aim to create an ultra-reactionary totalitarian state. Points to similarities between Hitler's political ideology and the alleged Jewish policy as presented in the "Protocols". Shows how Hitler uses antisemitism, which is widespread among the nations, to achieve his goals. Discusses the "Protocols" trial in Bern and its verdict, and calls for cessation of publication of the "Protocols" which has a catastrophic influence on the non-educated masses. The preface by Miliukov (pp. 7-45) summarizes the book, pointing out its importance for understanding the real goals of Hitler.